MENGEMBANGKAN KESEHATAN MENTAL DI LINGKUNGAN KELUARGA DAN SEKOLAH - Ifdil Ifdil (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
Mental health is one of the psychological phenomena found in many fields of life. Mental health is indicated by the existence of a condition that is psychologically prosperous. Individuals who have good mental health will be able to form and develop themselves into productive and effective individuals. The factors that affect mental health are factors from the family and school environment. Families contribute an important role in forming mentally healthy individuals. If a family experiences disharmony, it has the potential to bring mental disability to the family member. Furthermore, the condition of individuals who experience mental disability tend to be brought to the school environment so that it influences learning activities at school. Another thing that happened was also the emergence of psychological stress symptoms experienced by individuals in the school environment. Such conditions contribute greatly to the emergence of various misguided behaviors, psychological distress in the form of stress, depression, anxiety, trauma and PTSD in individuals. This article will describe the efforts to develop mental health in families and schools to build a mentally healthy society.